THE IMPLEMENTATION OF PROCESS-GENRE APPROACH TO TEACHING WRITING BUSINESS LETTER - Gupitasari, Hilda (2013)
This study reported on the implementation of process-genre approach to teaching writing business letter. The purposes of this study were to find out the extent to which the implementation of process-genre approach can improve writing ability of twelfth graders in writing business letter as well as what their responses to the use of process-genre approach are. This study was conducted based on Classroom Action Research (CAR) and it was designed into two cycles. Every cycle was composed of planning, acting, observing and reflecting. The participants were twelfth graders at one vocational school in Cianjur. The instruments employed were observation sheet, writing test and questionnaire. The result of this study demonstrated that there was an improvement in students' writing scores after conducting process-genre approach. The students' mean score in cycle 1 was 75 with 16 students (57.1%) gained scores above KKM. Meanwhile, the students' mean score in cycle 2 increased to 82.5 with 23 students (82.1%) got scores above KKM. Moreover, the questionnaire results also showed that process-genre approach could help the students in the process of writing application letter. Keywords: Process-genre approach, writing, application letter.